Education and training for sustainability. Towards Artificial Intelligence: an exploratory investigation on teachers. - Maria Vittoria Isidori; Henry Muccini; Alessio Santelli; Clara Evangelista (Firenze University Press, 2024)
The move towards a future green planet requires that we all learn to live and work in sustainable ways. Teacher professional learning is very important for innovation and sustainability in our education systems. The competent use of Artificial Intelligence (AI) in education is fundamental to achieve some sustainable development objectives through the training of new generations. From our survey of newly appointed teachers (responsible for active citizenship training) emerges the awareness of the role of AI in the ecological transition and in the development of a circular economy, the failure to apply AI in current teaching-training programming and the need to be trained on the use of AI and the risks of its improper use.   Educazione e formazione per la sostenibilità. Verso l'Intelligenza Artificiale: un'indagine esplorativa sui docenti. Il passaggio verso un futuro pianeta verde richiede che tutti impariamo a vivere e lavorare in modi sostenibili. L'apprendimento professionale degli insegnanti è molto importante per l'innovazione e la sostenibilità nei nostri sistemi educativi. L'uso competente dell'Intelligenza artificiale (IA) nell'istruzione è fondamentale per raggiungere alcuni obiettivi di sviluppo sostenibile attraverso la formazione delle nuove generazioni. Dalla nostra indagine su docenti neo immessi in ruolo (responsabili della formazione alla cittadinanza attiva) emerge la consapevolezza circa il ruolo dell'IA nella transizione ecologica e nello sviluppo di un'economia circolare, la mancata applicazione dell'IA nella programmazione didattico-formativa corrente e l'esigenza di essere formati sull'utilizzo dell'IA e sui rischi di un utilizzo improprio di essa.